1976
DOI: 10.1002/cpt1976194421
|View full text |Cite
|
Sign up to set email alerts
|

Antitussive activity of diphenhydramine in chronic cough

Abstract: A double-blind crossover study was conducted to evaluate the antitussive effectiveness of diphenhydramine (DPH) in chornic coughs related to bronchitis, at doses of 25 and 50 mg every 4 hr for four doses. Both 25- and 50-mg doses caused a statistically and clinically significant reduction in frequency of coughs, compared to placebo. The most frequently reported side effect was drowsiness, principally at the 50-mg dose level. There was little or no apparent correlation between antitussive effectiveness and inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…In a double-blind crossover study, diphenhydramine, administered in four 25-mg or 50-mg doses every 4 hours, induced a statistically and clinically significant reduction in cough frequency compared with placebo. Of note, although the most frequently reported side effect was drowsiness, especially with the 50-mg dose, there was little or no apparent correlation between the antitussive effect and the incidence of sedation (Lilienfield et al, 1976). In another randomized, double-blind study of patients with cough associated with allergic rhinoconjunctivitis, treatment with 10 mg daily doses of loratadine for 4 weeks resulted in significantly improved subjective ratings of cough frequency and cough intensity compared with placebo (Ciprandi et al, 1995).…”
Section: Drugs In Current Use For the Treatment Of Coughmentioning
confidence: 98%
“…In a double-blind crossover study, diphenhydramine, administered in four 25-mg or 50-mg doses every 4 hours, induced a statistically and clinically significant reduction in cough frequency compared with placebo. Of note, although the most frequently reported side effect was drowsiness, especially with the 50-mg dose, there was little or no apparent correlation between the antitussive effect and the incidence of sedation (Lilienfield et al, 1976). In another randomized, double-blind study of patients with cough associated with allergic rhinoconjunctivitis, treatment with 10 mg daily doses of loratadine for 4 weeks resulted in significantly improved subjective ratings of cough frequency and cough intensity compared with placebo (Ciprandi et al, 1995).…”
Section: Drugs In Current Use For the Treatment Of Coughmentioning
confidence: 98%
“…There were, however, two clinical trials (level 1b) in which adult volunteers developed potentially dose-related adverse effects after receiving chronic doses of diphenhydramine. In the first, doses of 100-200 mg diphenhydramine given over 16 hours were associated with symptoms including constipation, drowsiness, and mild anticholinergic effects (87). No serious toxicity was noted in any volunteer.…”
Section: Diphenhydramine: Chronic Exposures In Patients 6 Years Of Agmentioning
confidence: 96%
“…An older antihistamine would be effective in blocking this action while a newer, peripheral antihistamine would be ineffective. At present, the only evidence supporting the concept that central histaminergic pathways are important in the production of pathologic cough in humans are studies showing efficacy of older antihistamines as antitussives [8,25]. However, these molecules can have other activities at nonhistamine receptors.…”
Section: Possible Mechanisms By Which Older Antihistamines Could Inhimentioning
confidence: 99%
“…That study supported the concept that the sedative and antitussive potentials for antihistamines are unrelated. Furthermore, Lilienfield et al [25] showed that the cough-suppressant effect of diphenhydramine in patients with lower airway disease was unrelated to the sedative effects of this drug.…”
Section: Possible Mechanisms By Which Older Antihistamines Could Inhimentioning
confidence: 99%